Manajemen Proyek untuk Optimalisasi Teknologi Informasi dan Komunikasi dalam Pendidikan di SDN 013817 Sei Pasir - Farhan Graha Hidayat (CV Edujavare Publishing, 2024)
This study aims to optimize the use of information and communication technology (ICT) in learning at SDN 013817 Sei Pasir through an information technology project management approach. A descriptive qualitative method is used to illustrate the role of information systems in supporting data management at the school. Data was collected through observation and interviews. The results indicate that ICT utilization by teachers remains low. Supporting factors include an adequate number of teaching staff, while inhibiting factors involve limited ICT facilities and a lack of teacher skills in information technology.